Recurrent and Sustained Viral Infections in Primary Immunodeficiencies - Ruffner, Melanie A.; Sullivan, Kathleen E.; Henrickson, Sarah E. (Frontiers in Immunology, 2017)
Viral infections are commonplace and often innocuous. Nevertheless, within the population of patients with primary immunodeficiencies, viral infections can be the feature that drives a diagnostic evaluation or can be the most significant morbidity for the patient. This review is focused on the viral complication of primary immunodeficiencies. It will focus on respiratory viruses, the most type of viral infection in the general population. Children and adults with an increased frequency or severity of respiratory viral infections are often referred for an immunologic evaluation. The classic teaching is to investigate humoral function in people with recurrent sinopulmonary infections but this is often interpreted to mean recurrent bacterial infections. Recurrent or very severe viral infections may also be a harbinger of a primary immunodeficiency as well. This review will also cover persistent cutaneous viral infections, systemic infections, CNS infections and gastrointestinal infections. In each case, the specific viral infections may drive a diagnostic evaluation that is specific for that type of virus. This review also discusses the management of these infections which can become problematic in patients with primary immunodeficiencies.